2012
DOI: 10.1172/jci60016
|View full text |Cite
|
Sign up to set email alerts
|

Glucagonocentric restructuring of diabetes: a pathophysiologic and therapeutic makeover

Abstract: The hormone glucagon has long been dismissed as a minor contributor to metabolic disease. Here we propose that glucagon excess, rather than insulin deficiency, is the sine qua non of diabetes. We base this on the following evidence: (a) glucagon increases hepatic glucose and ketone production, catabolic features present in insulin deficiency; (b) hyperglucagonemia is present in every form of poorly controlled diabetes; (c) the glucagon suppressors leptin and somatostatin suppress all catabolic manifestations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
525
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 594 publications
(567 citation statements)
references
References 100 publications
(103 reference statements)
14
525
1
5
Order By: Relevance
“…Indeed, glucagon is known as a counterregulatory hormone that exerts a potent hyperglycaemic effect by increasing hepatic glucose output through the stimulation of both glycogenolysis and gluconeogenesis 9 . Some experimental data suggested that glucagon suppression or inactivation may provide therapeutic advantages over insulin monotherapy 10 . Many attempts have been developed to inhibit glucagon secretion and/or action, with the aim of improving glucose control in T2DM, however without obvious success so far except the success story of incretin-based therapies 11 .…”
Section: Wordsmentioning
confidence: 99%
“…Indeed, glucagon is known as a counterregulatory hormone that exerts a potent hyperglycaemic effect by increasing hepatic glucose output through the stimulation of both glycogenolysis and gluconeogenesis 9 . Some experimental data suggested that glucagon suppression or inactivation may provide therapeutic advantages over insulin monotherapy 10 . Many attempts have been developed to inhibit glucagon secretion and/or action, with the aim of improving glucose control in T2DM, however without obvious success so far except the success story of incretin-based therapies 11 .…”
Section: Wordsmentioning
confidence: 99%
“…Insulin counteracts ketogenesis by stimulating the use of glucose as primary energy source and by decreasing the release of FFA in the circulation (21). In contrast, glucagon stimulates ketogenesis, hepatic glucose production, and lipolysis (1,40). Changes in glucose metabolism are associated with adaptation of the number and/or function of ␤-cells to produce and secrete an adequate amount of insulin (6,34).…”
mentioning
confidence: 99%
“…T he glucagon receptor (GCGR) is a member of the class B G protein-coupled receptor (GPCR) family (1) that mediates the activity of glucagon, a pancreatic islet-derived peptide hormone that plays a central role in the pathophysiology of diabetes (2). Several GCGR antagonists that improve glycemic control in animal models of diabetes and diabetic patients have been described (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%